2010
DOI: 10.1007/s10096-010-1050-8
|View full text |Cite
|
Sign up to set email alerts
|

Fungicidal activity of thymol and carvacrol by disrupting ergosterol biosynthesis and membrane integrity against Candida

Abstract: Natural isopropyl cresols have been reported to have antifungal activity. This work is an attempt to examine thymol and carvacrol against 111 fluconazole-sensitive and -resistant Candida isolates. Insight into the mechanism of action was elucidated by flow cytometric analysis, confocal imaging and ergosterol biosynthesis studies. The susceptibility tests for the test compounds were carried out in terms of minimum inhibitory concentrations (MICs), disc diffusion assays and time-kill curves against all Candida i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
192
3
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 342 publications
(223 citation statements)
references
References 21 publications
11
192
3
8
Order By: Relevance
“…[11][12][13][14][15][16] The mode of action of thymol against yeast and fungi has been sparsely investigated, though certain studies point to interactions with the cell envelope and intracellular targets. [16][17][18][19] Thymyl derivatives are well represented in Asteraceae plants, particularly within tribes Senecioneae, Eupatorieae, Inuleae and Helenieae. In some Inula, Doronicum and Pulicaria species, thymyl derivatives rather than sesquiterpenoids are the major root constituents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14][15][16] The mode of action of thymol against yeast and fungi has been sparsely investigated, though certain studies point to interactions with the cell envelope and intracellular targets. [16][17][18][19] Thymyl derivatives are well represented in Asteraceae plants, particularly within tribes Senecioneae, Eupatorieae, Inuleae and Helenieae. In some Inula, Doronicum and Pulicaria species, thymyl derivatives rather than sesquiterpenoids are the major root constituents.…”
Section: Introductionmentioning
confidence: 99%
“…Keeping in view diverse pharmacological activities of thymol [7][8][9][10][11][12][13][14][15][16][17][18][19] and preliminary results on bioactivity of thymyl derivatives 4,5,22,25,[28][29][30]33 we have set the aim of our study. By making a single modification of a phenolic functionality in thymol we have obtained a series of ester compounds (3a-t), performed their structural characterization, in vitro antimicrobial testing and in silico calculation of physico-chemical, pharmacokinetic and toxicological properties.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that some EOs exhibit the highest potential against Candida species [31,32] and aspergillus sp. [32,33].…”
Section: Composition and Mechanism Of Antimicrobial Action Of Essentimentioning
confidence: 99%
“…Several of these plant products have significant antimicrobial properties [2,13,14]. Thymol and carvacrol are two potent antifungal agents found abundantly in essential oils of plants like thyme and organo [15]. They have excellent antifungal properties with low MIC values and negligible cytotoxicity.…”
mentioning
confidence: 99%
“…These results were in concurrence with the observed changes in the accumulation and efflux of R6G and Hoescht 33342 dyes by Candida cells treated with thymol and carvacrol. Although some results show upregulation of these genes in the presence of thymol [20][21][22], we can say that these natural antifungals may not specifically impair expression of the transporters but their fungicidal activity may include inhibition of the plasma membrane proton efflux pump and disruption of membrane integrity [13,15]. Inhibition of drug efflux pumps using natural plant products seems to be excellent strategy for overcoming or rather reversing drug resistance in pathogenic fungal species.…”
mentioning
confidence: 99%